Convergence of Implicit and Explicit Schemes for an Asymptotically Nonexpansive Mapping in 𝑞-Uniformly Smooth and Strictly Convex Banach Spaces - Meng Wen; Changsong Hu; Zhiyu Wu (Journal of Applied Mathematics)
We introduce a new iterative scheme with Meir-Keeler contractions for an asymptotically nonexpansive mapping in 𝑞-uniformly smooth and strictly convex Banach spaces. We also proved the strong convergence theorems of implicit and explicit schemes. The results obtained in this paper extend and improve many recent ones announced by many others.